Variation in the Diagnosis and Management of Appendicitis at Canadian Pediatric Hospitals. (30th June 2015) - Thompson, Graham C.; Schuh, Suzanne; Gravel, Jocelyn; Reid, Sarah; Fitzpatrick, Eleanor; Turner, Troy; Bhatt, Maala; Beer, Darcy; Blair, Geoffrey; Eccles, Robin; Jones, Sarah; Kilgar, Jennifer; et al.
Abstract Objectives The objective was to characterize the variations in practice in the diagnosis and management of children admitted to hospitals from Canadian pediatric emergency departments (EDs) with suspected appendicitis, specifically the timing of surgical intervention, ED investigations, and management strategies. Methods Twelve sites participated in this retrospective health record review. Children aged 3 to 17 years admitted to the hospital with suspected appendicitis were eligible. Site‐specific demographics, investigations, and interventions performed were recorded and compared. Factors associated with after‐hours surgery were determined using generalized estimating equations logistic regression. Results Of the 619 children meeting eligibility criteria, surgical intervention was performed in 547 (88%). After‐hours surgery occurred in 76 of the 547 children, with significant variation across sites (13.9%, 95% confidence interval = 7.1% to 21.6%, p < 0.001). The overall perforation rate was 17.4% (95 of 547), and the negative appendectomy rate was 6.8% (37 of 547), varying across sites (p = 0.004 and p = 0.036, respectively). Use of inflammatory markers (p < 0.001), blood cultures (p < 0.001), ultrasound (p = 0.001), and computed tomography (p = 0.001) also varied by site. ED administration of narcotic analgesia and antibiotics varied across sites (p < 0.001 and p = 0.001, respectively), as did the type of surgical approach (p < 0.001). After‐hours triage had a significant inverse association with after‐hours surgery (p = 0.014). Conclusions Across Canadian pediatric EDs, there exists significant variation in the diagnosis and management of children with suspected appendicitis. These results indicate that the best diagnostic and management strategies remain unclear and support the need for future prospective, multicenter studies to identify strategies associated with optimal patient outcomes.